Literature Review on the Scope of Macroeconomics Key Concepts, Theories, and Contemporary Issues - Aszra Iman Farzana (CV Pena Jaya Pers, 2025)
Macroeconomics, as a pivotal branch of economic science, examines aggregate economic phenomena such as national income, employment levels, price stability, economic growth, and balance of payments, distinguishing itself from microeconomics by focusing on economy-wide interactions rather than individual agents. This literature review synthesizes key scholarly works to delineate the scope of macroeconomics, tracing its theoretical evolution from classical foundations emphasizing market self-regulation and Say's Law through Keynesian revolutions that introduced demand-side management and government intervention, to modern paradigms like New Classical, New Keynesian, and Real Business Cycle theories, which incorporate rational expectations, microfoundations, and supply- side shocks. The review highlights core concepts including Gross Domestic Product (GDP) measurement and its circular flow, inflation-unemployment trade-offs via the Phillips Curve, fiscal and monetary policy instruments for stabilization, and international macro issues like exchange rates and trade balances. Drawing from seminal sources such as policy overviews, historical research trajectories, and NBER analyses of contemporary models, it identifies persistent debates on policy effectiveness post-global financial crises and amid digital transformations, including post-COVID recovery dynamics and sustainable growth challenges. Despite advancements, gaps remain in integrating behavioral insights, climate risks, and technological disruptions into macroeconomic frameworks, underscoring the need for interdisciplinary approaches. This synthesis not only maps the expansive terrain of macroeconomic inquiry but also offers implications for policymakers in emerging economies like Indonesia, advocating adaptive strategies to foster stability and inclusive growth. Future research should prioritize empirical validations of hybrid models to address evolving global uncertainties.